Safety and feasibility of early single‐dose mitomycin C bladder instillation after robot‐assisted radical nephroureterectomy. (9th August 2020) - Gulamhusein, Aziz; Silva, Pedro; Cullen, David; Tran, Maxine; Mumtaz, Faiz; Patki, Prasad; Barod, Ravi; Bex, Axel
Abstract : Objectives: To assess the safety and feasibility of early single‐dose mitomycin C (MMC) bladder instillation after robot‐assisted radical nephroureterectomy (RARNU) at a tertiary kidney cancer centre. RARNU with bladder cuff excision and subsequent MMC bladder instillation to reduce recurrence risk is the 'gold standard' for high‐risk upper urinary tract urothelial carcinoma (UUTUC). We adapted a RARNU technique with precise distal ureteric dissection, bladder cuff excision and watertight bladder closure. Patients and Methods: We retrospectively reviewed all patients undergoing RARNU for UUTUC at our centre performed as a standardised transperitoneal procedure comprising of: bladder cuff excision, two‐layer watertight closure and intraoperative bladder leak test; without re‐docking/re‐positioning of the robotic surgical system. Patient demographics, the timing of MMC instillation, adverse events (surgical and potentially MMC‐related) and length of stay (LOS) were assessed according to the Clavien–Dindo classification. Results: A total of 69 patients underwent a RARNU with instillation of MMC. The median (interquartile range [IQR]) age was 70 (62–78) years. The median (IQR) day of MMC instillation was 2 (1–3) days and the median (IQR) LOS was 2 (2–4) days, with urethral catheter removal on day of discharge in all cases. Only Grade I Clavien–Dindo complications occurred in seven patients (10%); five had ileus, one a wound infection and one a self‐limiting delirium, all managed conservatively. No adverse events potentially related to MMC instillation were noted within 30 days postoperatively. Conclusion: The use of intravesical MMC instillation given in the immediate postoperative period appears feasible and safe in patients undergoing RARNU with intraoperative confirmation of a water‐tight closure ensuring early catheter‐free discharge, with no significant adverse events. The potential reduction in intravesical recurrence in patients receiving early MMC needs to be assessed with longitudinal follow‐up studies.